Early results from the galactic O-star spectroscopic survey: C III emission lines in of spectra - Walborn, Nolan Revere (2010)
On the basis of an extensive new spectroscopic survey of Galactic O stars, we introduce the Ofc category, which consists of normal spectra with C III λλ4647-4650-4652 emission lines of comparable intensity to those of the Of defining lines N III λλ4634-4640-4642. The former feature is strongly peaked to spectral type O5, at all luminosity classes, but preferentially in some associations or clusters and not others. The relationships of this phenomenon to the selective C III λ5696 emission throughout the normal Of domain, and to the peculiar, variable Of?p category, for which strong C III λλ4647-4650-4652 emission is a defining characteristic, are discussed. Magnetic fields have recently been detected on two members of the latter category. We also present two new extreme Of?p stars, NGC 1624-2 and CPD -28° 2561, bringing the number known in the Galaxy to five. Modeling of the behavior of these spectral features can be expected to better define the physical parameters of both normal and peculiar objects, as well as the atomic physics involved.